Model Stimulus-Organism-Response: Penentu Perilaku Pembelian Konsumen Secara Situasional - Nonie Magdalena (Jurnal Manajemen Maranatha, 2005)
Understanding about consumer purchase behavior is an essential aspect for developing organization bussiness strategic, especially in retailing. S-O-R (Stimulus-Organism-Response) model helps the practision and academics to understand which stimulus will influence consumers and the reaction that comsumer gave. One of the stimulus that explained in this article is the situation. Situation is an aspect that had change and hardly to predict. In other words, situation will determine consumer purchasing behavior. The emphazise of this situation are the consumption situation and purchase situation.